Wild Islands - Ganeri, Anita 1961-; Phillips, Mike 1961- (London ; New York : Scholastic, 2010)
Geography with the gritty bits left in! Does geography grind you down? Fed up with miserable maps, rotten rock piles and gruelling graphs? Wave goodbye to boring geography lessons as you are cast away on the far-flung shores of Wild Islands. Marvel as a brand-new island pops up from the sea. Gasp at the hot-tempered island that blew its top. Choke on the smell of an island dragon's foul breath. And if that's not wild enough for you, discover where to find coconuts with magical powers, try to crack the case of the missing island, and read the remarkable story of a real-life Robinson Crusoe. It's earth-shatteringly exciting! Geography has never been so horrible!
R
800
R
Keywords: Islands -- Juvenile literature; Castaways -- Juvenile literature; Castaways; Islands; Juvenile works